New horizons in cardiovascular magnetic resonance imaging - Partovi, Sasan; Karmonik, Christof (Cardiovascular Diagnosis and Therapy, 2014)
This issue of ‘Cardiovascular Diagnosis and Therapy (CDT)’ has a special focus on application and development of magnetic resonance imaging (MRI) in cardiovascular diseases. The challenges associated with imaging of the heart and the huge disease burden associated with cardiovascular diseases has been one of the major motivations in the last few years for the development of new MRI techniques. A realm of new pulse sequences, either focusing on ‘freezing’ motion or on providing improved endogenous contrast mechanisms were developed in this context and are now being evaluated in clinical and preclinical research efforts focusing on the heart and vascular circulation.